Familial aggregation of human infection with Schistosoma japonicum in the Poyang Lake region, China - Ellis, Magda K. (2005)
Despite the success of extensive control measures that have been implemented in China for over 50 years, the number of individuals infected with Schistosoma japonicum remains high in the remaining endemic areas. A variance components analysis was undertaken to estimate the heritable and environmental components that contribute to S. japonicum infection in the Poyang Lake region of Jiangxi Province, PR China. The total target population was 3148 from four separate administrative villages. Two thousand seven hundred and five of these comprised 400 families ranging in size from 3 to 188. After adjustments were made for gender, water contact and past history of having had schistosomiasis, the heritable component was estimated to account for as much as 58% of the phenotype variation under the polygenic model. Household was not shown to be an important environmental factor. Incorporating village effects indicated that the results were valid for the total population. We conclude that genetic heritability in this region is high and plays an important role in determining risk of infection with S. japonicum.